Is It Safe to Switch From Intravenous Immunoglobulin to Subcutaneous Immunoglobulin in Patients With Common Variable Immunodeficiency and Autoimmune Thrombocytopenia? - Scheuerlein, Philipp; Pietsch, Larissa; Camacho-Ordonez, Nadezhda; Reiser, Veronika; Patel, Smita; Burns, Siobhan O.; Warnatz, Klaus; Grimbacher, Bodo (Frontiers in Immunology, 2018)
Background. A significant amount of common variable immunodeficiency (CVID) patients manifest with autoimmunity. Particularly, autoimmune thrombocytopenia (AITP) is commonly seen. Intravenous immunoglobulins (IVIG) are an established treatment option for both, CVID and AITP. Nonetheless, due to fewer systemic side effects, immunoglobulins are increasingly applied subcutaneously (SCIG). Objective. To compare the efficacy and safety of IVIG and SCIG treatment in patients with both CVID and clinical relevant thrombocytopenia in the prevention of AITP bouts. Methods. Patients with both CVID and AITP were enrolled at the Centre for Chronic Immunodeficiency in Freiburg, Germany and at the Royal Free Hospital, London, UK. Clinical and laboratory features of patients were collected and analyzed. Results. This retrospective study recruited 61 adult patients between 19 and 71 years of age who had a diagnosis of CVID and at least one bout of thrombocytopenia defined as a platelet count of <50.000/µl if bleeding episodes occurred, or a platelet count of <20.000/l without bleeding . Thirty patients received immunoglobulin through IVIG and thirty-one patients were on SCIG replacement. One patient of the IVIG-group was excluded, because of a diffuse large B-cell lymphoma. We did not find a higher occurrence of thrombocytopenic events in CVID patients who received SCIG, compared to CVID patients who had IVIG, but we identified a low IgG through level as a risk factor for AITP bouts. Conclusion. SCIG is at least as safe as IVIG for patients with CVID and concomitant AITP. However, an IgG through-level under 7g/l is a key factor for the development of AITP.